Classification of Dissertations in the Graduate Program in Environmental Sciences According to the Sustainable Development Goals (SDGs) - Milkievicz, Indianara Ignacio; Borges, Vitor Toledo; Fagundes, Alexandre Borges; Simioni, Flávio José (Revista ft, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista ft (e-ISSN: 1678-0817) ON 2025-01-31, AVAILABLE ONLINE: https://dx.doi.org/10.69849/revistaft/pa10202501310818 Abstract Aligning scientific research with the Sustainable Development Goals (SDGs) is essential for addressing global environmental and social challenges. This article presents a systematic review of dissertations from the Graduate Program in Environmental Sciences (PPGCAMB), categorizing them based on the UN SDGs. Chat PDF was utilized for efficient document screening and reading, while IRAMUTEQ software facilitated quantitative analysis and data categorization. The classification highlights the most addressed SDGs and reveals thematic gaps within the program, summarized in a straightforward table. This study's practical application enhances PPGCAMB’s alignment with the Sustainable Development Goals and provides a data-driven basis for strategic research planning. To increase the academic impact on public policies and sustainable solutions, it is advisable to expand the analysis to incorporate social and environmental impact metrics and foster inter-institutional collaborations.
Keywords: Sustainability; Scientific analysis; Environmental development; Thematic classification; Environmental education